Removal of Chromium(III) by the Adsorbents Produced from Coal Mining Wastes - Mahramanlioglu, Mehmet; Guclu, Kubilay; Misirli, Tolga (Asian Journal of Chemistry, 2010)
The adsorption study of Cr(III) on the adsorbent produced from coal mining waste was carried out as a function of time, initial concentration and pH. The Lagergren equation was used to calculate the adsorption rate constant. The equlibrium data showed that the adsorption of Cr(III) obeyed the Langmuir and Freundlich isotherm equations. Based on the Langmuir isotherm constant it was shown that the adsorbent produced from coal mining waste was more effective compared to most of the other adsorbents. The maximum adsorption for Cr(III) was observed at pH 5.2. Column studies were also performed to simulate the industrial conditions and column capacities for each flow rate were determined.